Analysis of environmental factors affecting the incidence of testicular cancer, with particular emphasis on testicular germ cell tumors (TGCTs). Literature review - Ptak, Anita; Szyc, Michał (Quality in Sport, 2024)
Introduction: Testicular cancer is the most common malignancy among men in the 20-44 age group. Most of the incidence is testicular germ cell tumor. In recent years there has been a steady increase in the incidence of this cancer. For this reason, we analyzed available articles on environmental risk factors that may influence the incidence of increased testicular malignancies Material and methods: Review of the specialized literature in the field of urology and articles available on PubMed, searching by the keywords “testicular cancer,” “testicular cancer risk factors,” “germ cell tumor,” “tgct‘’ Aim of the study: The purpose of the study is to review the available literature and research papers regarding risk factors for malignant tumors of the testis. Summary: In recent years, there has been an increase in the incidence of testicular cancer, especially among men aged 20-44 years. The vast majority of it is germ cell tumors (TGCT). This article discusses the influence of environmental factors on the development of testicular cancer, with particular emphasis on the induction of TGCT. Studies indicate an association between exposure to trichloroethylene and other solvents and the risk of TGCT induction. The role of exposure to pesticides (especially fungicides), organic chlorine compounds, and viruses was also indicated to increase the risk of developing TGCTs,. The association of neoplasia with marijuana and tobacco use has also been studied, but needs further research. There is a need for continued research regarding heavy metals, infertility and factors related to pregnancy and the perinatal period. It is necessary to know the mechanisms that induce the process of carcinogenesis in the testis, which will enable the use of prevention and prophylaxis.